Let Me Tell You About My Success: The Implications of Attribution-Based Capitalization Response Messages for Discloser Affect. Issue 3 (26th May 2016) - Roth, Rebecca; Holmstrom, Amanda J.
Abstract : Capitalization attempts, or the sharing of personal good news, can have positive outcomes for disclosers when met with a skillful response. This study reports on a test of an attribution-based theoretical framework for capitalization response messages. Participants ( N = 314) read capitalization response messages created by crossing the causal attribution dimensions of locus, stability, and globality. They rated messages for their anticipated effect on positive and negative affect. Results indicate that messages that make internal attributions for success are rated significantly higher on positive affect and lower on negative affect than messages making external attributions, as are messages making stable versus unstable attributions. The stability dimension moderates the impact of the globality dimension on message ratings. Implications for attribution and social support theories are discussed.